Per una formazione al lavoro Le sfide della disabilità adulta - Falconi, Sabina; Boffo, Vanna; Zappaterra, Tamara (Strumenti per la didattica e la ricerca, 2012)
The volume is a collection of the papers from a study seminar held at the University of Florence Faculty of Education and Training Sciences in March 2012 entitled Formazione e orientamento al lavoro. Le sfide della disabilità adulta. The aim of the initiative was to highlight a topic/problem which has little or no resonance in civil society, or in study and research contexts, namely, training and career guidance for disabled adults. The volume also recounts a course of studies carried out by Le Rose, a cooperative from the municipality of Florence, involving empirical research on the relationship between disability and job placement. As well as proposing an interdisciplinary and multifaceted reflection on a definitely innovative topic, the intention is to emphasize the central place of work in the lives of all people and the role that suitable education and training plays in constructing the adult identity. Care for the place where the job training is carried out, as well as attention to the relationships and actions pursued by the workers undertaking to develop job placement programmes, are central dimensions for the construction of a renewed culture of inclusion, citizenship and social and personal recognition.